Completeness of maternal smoking status recording during pregnancy in United Kingdom primary care data - Dhalwani, Nafeesa N.; Tata, Laila J.; Coleman, Tim; Fleming, Kate M.; Szatkowski, Lisa (Public Library of Science, 2013)
Background: Given the health impacts of smoking during pregnancy and the opportunity for primary healthcare teams to encourage pregnant smokers to quit, we assessed the completeness of gestational smoking status recording in primary care data and investigated whether completeness varied with women’s characteristics. Methods: In The Health Improvement Network (THIN) database we calculated the proportion of pregnancies ending in live or stillbirths where there was a recording of maternal smoking status for each year from 2000 to 2009. Logistic regression was used to assess variation in the completeness of maternal smoking recording by maternal characteristics, before and after the introduction of the QOF. Results: Women had a record of smoking status during the gestational period in 28% of the 277,552 pregnancies identified. In 2000, smoking status was recorded in 9% of pregnancies, rising to 43% in 2009. Pregnant women from the most deprived group, measured using the Townsend Index of deprivation, were 17% more likely to have their smoking status recorded than pregnant women from the least deprived group before QOF implementation (OR 1.17, 95% CI 1.10-1.25) and 42% more likely afterwards (OR 1.42, 95% CI 1.37-1.47). A diagnosis of asthma was related to recording of smoking status during pregnancy in both the pre-QOF (OR 1.63, 95% CI 1.53-1.74) and post-QOF periods (OR 2.08, 95% CI 2.02-2.15). There was no association between having a diagnosis of diabetes and recording of smoking status during pregnancy pre-QOF however, post-QOF diagnosis of diabetes was association with a 12% increase in recording of smoking status (OR 1.12, 95% CI 1.05-1.19). Conclusion: Recording of smoking status during pregnancy in primary care data is incomplete though has improved over time, especially after the implementation of the QOF, and varies by maternal characteristics and QOF-incentivised morbidities.